Governance in Indonesia Banking Industries as an Effort to Improve their National Competitiveness - Erida Herlina (Journal of Economics, Business, and Accountancy Ventura, 2017)
The bank’s transparency of their financial performance has been demanded by the public so that the banks have to demonstrate their products and activities. The banks’ health level assessment, currently being enacted by Bank Indonesia is a risk approach that includes Risk Profile, Good Corporate Governance, Earning, and Capital (RGEC). The more Good Corporate Governance (GCG) assessment is geared today for the banks to strengthen their competitive position and increase investor confidence. This study is directed to test the accounting conservatism towards GCG as well as the consequence of GCG on the financial performance, Corporate Social Responsibility (CSR) and information asymmetry. This study used financial data published on the Indonesia Stock Exchange in 2008-2015 and 152 samples were taken from 19 banks data and tested using simple regression. The results show that Good Corporate Governance has an impact on financial performance, Corporate Social Responsibility, and information asymmetry. The better governance carried out by the banking system will have an impact on their competitiveness in an effort to increase public confidence to invest their funds.